Implementasi Model Sinektik Berbasis AMTSAL dalam Pembelajaran PAI - Giyarsi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
Islamic education aims to realize muslim people who believe, are godfearing, and knowledgeable who are able to devote themselves to God with an attitude and a complete personality submit themselves in all aspects of life in order to seek the pleasure of God. These objectives can be achieved through students' understanding of PAI materials. Optimizing the preparation of learning models is one of the main factors that can help improve learning outcomes. Thus, to improve the learning outcomes of PAI subjects among students, the innovation of learning models in schools needs to pay attention to the characteristics and needs of students according to the related materials. A systematic and interesting learning model is one of the things that can support the achievement of expected competencies. Synectic learning model becomes one of the strategies that can improve pai learning results. The rationale of this model is that metaphorical activities that include personal analogies, direct analogies, and compacted conflicts can help students understand abstract concepts of PAI material, especially about beliefs.